Respostas

A melhor resposta!
  • Usuário do Brainly
2014-07-24T10:53:25-03:00
Z=a+bi  ~~> a = 1  ; b = √3

z= 1 + √3i

p² = 1² + 
 (√3)²
p²= 1 + 3
p² = 4
p=2   

cos
θ= a / p
~~>a= cosθ.p

sen
θ = b / p
~~>b=senθ . p

sen
θ = b/p
senθ=√3 / 2
θ = π  / 3  ( a e b positivos, ângulo é do primeiro quadrante )

z=a + bi
z=2.cosπ/3 + senπ/3 . 2 .i
z=2( cos
π/3 + i . senπ/3 )
z
⁹=2⁹ ( cos9π/3 + i.sen.9π/3 )
z⁹=510 ( cos3π + i.sen3π )
z⁹ = 510 ( cos540 + i.sen540 )
z⁹ = 510 (-cos0 + i,sen0)
z⁹ = 510.(-1)
z⁹= -510 
1 5 1
  • Usuário do Brainly
2014-07-24T11:24:23-03:00
Z¤ = - 510
Espero ter ajudado ! Bons Estudos ;-)